Predicting Dropout in Higher Education: a Systematic Review - Silva, Jailma Januário da; Roman, Norton Trevisan (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2021: Anais do XXXII Simpósio Brasileiro de Informática na Educação, 2021)
In this article, we present a systematic literature review, carried out from February to March 2020, on the application of a machine learning technique to predict student dropout in higher education institutions. Besides describing the protocol followed during our research, which includes the research questions, searched databases and query strings, along with criteria for inclusion and exclusion of articles, we also present our main results, in terms of the attributes used by current research on this theme, along with adopted approaches, specific algorithms, and evalution metrics. The Decision Tree technique is the most used for the construction of models, and accuracy and recall and precision being the most used metric for evaluating models.